Antimicrobial activity of ZnO nanoparticles against pathogenic bacteria and fungi - Navale, G. R.; Thripuranthaka, M.; Late, Dattatray J.; Shinde, Sandip S. (JSM Nanotechnology and Nanomedicine, 2014)

One molecule of ionic liquid and tert-alcohol on a polystyrene-support as catalysts for efficient nucleophilic substitution including fluorination - Shinde, Sandip S.; Patil, Sunil N. (Organic & Biomolecular Chemistry, 2014)
The tert-alcohol and ionic liquid solvents in one molecule [mim-(OH)-O-t][OMs] was immobilized on polystyrene and reported to be a highly efficient catalyst in aliphatic nucleophilic substitution using alkali metal salts. Herein, we investigated the catalytic activity of a new structurally modified polymer-supported tert-alcohol functionalized imidazolium salt catalyst in nucleophilic substitution of 2-(3-methanesulfonyl-oxypropyoxy) naphthalene as a model substrate with various metal nucleophiles. The tert-alcohol moiety of the ionic liquid with a hexyl chain distance from polystyrene had a better catalytic activity compared to the other resin which lacked an alkyl linker and tert-alcohol moiety. We found that the maximum [mim-(OH)-O-t][OMs] loading had the best catalytic efficacy among the tested polystyrene-based ionic liquids (PSILs) in nucleophilic fluorination. The catalytic efficiency of the PS[him-(OH)-O-t][OMs] as a phase transfer catalyst (PTC) was determined by carrying out various nucleophilic substitutions using the corresponding alkali metal salts from the third to sixth periodic in CH3CN or tert-BuOH media. The scope of this protocol with primary and secondary polar substrates containing many heteroatoms is also reported. This PS [him-(OH)-O-t][OMs] catalyst not only enhances the reactivity of alkali metal salts and reduces the formation of by-products but also affords high yield with easy isolation.

Antibiofilm activity of tert-BuOH functionalized ionic liquids with methylsulfonate counteranions - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (RSC Advances, 2015)
A series of varying alkyl chain length substituted tert-BuOH-functionalized-imidazolium mesylate salts [alkyl-(t)OHim][OMs] were synthesized and evaluated for antimicrobial activity and antibiofilm potential on selected pathogenic microorganisms including bacteria (Gram positive and Gram negative), yeast, and fungi. The dodecyl substituted ionic liquid [C-12-(t)OHim][OMs] significantly prevented the biofilm formation of S. epidermidis at 100 mu M concentration as well as showed noteworthy antimicrobial activity. We conclude that the ionic liquids (ILs) bearing chain lengths lower than the dodecyl length were found to be less effective against most of the tested pathogenic microorganisms.

Dinuclear salen cobalt complex incorporating Y(OTf)(3): enhanced enantioselectivity in the hydrolytic kinetic resolution of epoxides - Patel, Deepak; Kurrey, Ganesh Ram; Shinde, Sandip S.; Kumar, Pradeep; Kim, Geon-Joong; Thakur, Santosh Singh (RSC Advances, 2015)
The activation of inactive Jacobsen's chiral salen Co(II) (salen = N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine) compound is attained by dinuclear chiral salen Co(III)-OTf complex formation with yttrium triflate. The yttrium metal not only displays a promoting effect on electron transfer, but also assists in forming two stereocentres of a Lewis acid complex with Co(III)-OTf. We found that the binuclear Co-complex significantly enhanced reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its analogous monomer and kinetic data are also consistent with these results.

Mild regiospecific alcoholysis and aminolysis of epoxides catalyzed by zirconium(IV) oxynitrate - Shinde, Sandip S.; Said, Madhukar S.; Surwase, Trupti B.; Kumar, Pradeep (Tetrahedron Letters, 2015)
A regiospecific method for the ring-opening reaction of epoxides by the primary, secondary, tertiary alcohols, and aryl, aliphatic amines has been developed using non-toxic metal nitrate salt as a catalyst. The best results were obtained using zirconium(IV) oxynitrate among the various screened metal nitrate salts. The reported protocol works efficiently for styrene epoxide and aliphatic as well. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alcoholysis; Aminolysis; Epoxide; Lewis acid; Zirconia

Nucleophilic fluorination using imidazolium based ionic liquid bearing tert-alcohol moiety - Shinde, Sandip S.; Patil, Sunil N.; Ghatge, Amruta; Kumar, Pradeep (New Journal of Chemistry, 2015)

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids

Stereoselective quenching of cedryl carbocation in epicedrol biosynthesis - Shinde, Sandip S.; Navale, Govinda R.; Said, Madhukar S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Epicedrol synthase catalyzes the cyclization of achiral diphosphate substrate, (E,E)-farnesyldiphosphate (FPP) into epicedrol. GC-MS analysis of assay extracts obtained by incubating FPP with epicedrol synthase in 21.6 at % H2(18)O buffer showed the molecular ion of 224 for epicedrol. The labeled oxygen study presented here unambiguously demonstrates that the hydroxyl group of the epicedrol synthase enzymatic product, epicedrol, is derived from a water molecule, not from the phosphate moiety of the FPP. (C) 2016 Elsevier Ltd. All rights reserved.

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Cyclization mechanism of phomopsene synthase: mass spectrometry based analysis of various site-specifically labeled terpenes - Shinde, Sandip S.; Minami, Atsushi; Chen, Zhi; Tokiwano, Tetsuo; Toyomasu, Tomonobu; Kato, Nobuo; Sassa, Takeshi; Oikawa, Hideaki (Journal of Antibiotics, 2017)
Elucidation of the cyclization mechanism catalyzed by terpene synthases is important for the rational engineering of terpene cyclases. We developed a chemoenzymatic method for the synthesis of systematically deuterium-labeled geranylgeranyl diphosphate ( GGPP), starting from site-specifically deuterium-labeled isopentenyl diphosphates (IPPs) using IPP isomerase and three prenyltransferases. We examined the cyclization mechanism of tetracyclic diterpene phomopsene with phomopsene synthase. A detailed EI-MS analysis of phomopsene labeled at various positions allowed us to propose the structures corresponding to the most intense peaks, and thus elucidate a cyclization mechanism involving double 1,2-alkyl shifts and a 1,2-hydride shift via a dolabelladien-15-yl cation. Our study demonstrated that this newly developed method is highly sensitive and provides sufficient information for a reliable assignment of the structures of fragmented ions.

Mechanistic study of nucleophilic fluorination promoted by tri-tert-butanolamine - Lee, Sung-Sik; Jung, Hyun-Kyung; Shinde, Sandip S.; Lee, Sungyul (Journal of Fluorine Chemistry, 2017)
Quantum chemical study is carried out to elucidate the mechanism of S(N)2 fluorination using. CsF promoted by tri-tert-butanolamines. Focus is on the role of the hydroxyl (OH) and the amine functional groups for accelerating the reaction. Our systematic analysis indicates that the OH groups form strong interactions with the nucleophile F-. Thus, it seems that hydrogen bonding with the nucleophile may accelerate the S(N)2 processes rather than retard them, as conventional wisdom suggests. The origin of the experimentally observed improvement of the promotor efficiency in t-butanol solvent over that in CH3CN is examined. We show that the coordination of the solvent t-butanol molecule as Lewis base on the counter-cation Cs+ lowers the Gibbs free energy of activation. (C) 2017 Elsevier B.V. All rights reserved.

Molybdenum oxide-mediated facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Khandare, Leena; Shinde, Sandip S. (Tetrahedron Letters, 2017)

Tri-tert-butanolamine as an organic promoter in nucleophilic fluorination - Shinde, Sandip S.; Khonde, Nilesh; Kumar, P. (ChemistrySelect, 2017)
Tri-tert-butanol amine acts as promoter with alkali metal salts in the nucleophilic fluorination of alkylsulfonates. It significantly enhances the reactivity of alkali metal salts with minimum formation of side-products (alkene, ether, and alcohol) com-pared to other catalysts in fluorination reaction. The synergism of tert-alcohol and amine moiety plays a pivotal role in fluorination.

Enzymatic formation of a skipped methyl‐substituted octaprenyl side chain of longestin (KS‐505a): involvement of homo‐IPP as a common extender unit - Taro Ozaki; Shinde, Sandip S.; Gao, Lei; Okuizumi, Ryo; Liu, Chengwei; Ogasawara, Yasushi; Lei, Xiaoguang; Dairi, Tohru; Minami, Atsushi; Oikawa, Hideaki (Angewandte Chemie, 2018)
Longestin (KS‐505a), a specific inhibitor of phosphodiesterase, is a meroterpenoid that consists of a unique octacyclic terpene skeleton with branched methyl groups at unusual positions (C1 and C12). The biochemical analysis of Lon23, a methyltransferase involved in the biosynthesis of longestin, demonstrated that methylation of IPP afforded 3Z‐3‐methyl IPP. This compound as well as IPP was selectively accepted as extender units by Lon22, a geranylgeranyl diphosphate (GGPP) synthase homolog, to yield dimethylated GGPP (dmGGPP). Absolute configuration of dmGGPP was determined to be (4R, 12R) by degradation and chiral GC analysis. These findings led us to propose key steps of the biosynthetic pathway of the unusual homoterpenoid longestin.

Sucrose capped gold nanoparticles as a plasmonic chemical sensor based on non-covalent interactions: application for selective detection of vitamins B-1 and B-6 in brown and white rice food samples - Shrivas, Kamlesh; Nirmalkar, Nidhi; Thakur, Santosh Singh; Deb, Manas Kanti; Shinde, Sandip S.; Shankar, Ravi (Food Chemistry, 2018)
We report simple and selective method for detection of vitamins B-1 and B-6 in brown and white rice samples using localized surface plasmon resonance (LSPR) of sucrose capped gold nanoparticles (AuNPs) as a chemical sensor colorimetrically. Here, detection is based on the color change of AuNPs from pink to blue followed by a red shift of LSPR absorption band in UV-vis region with the addition of vitamins B-1 and B-6 into the NPs solution. A good linear range was observed in the range of 25-1000 ngmL(-1) with detection limit of 8 ngmL(-1) for B-1 and 50-1000 ngmL(-1) with detection limit of 15 ngmL(-1) for vitamins B-6. The employment of AuNPs for detection of B-1 and B-6 vitamins in rice food samples showed remarkable abilities in terms of the simplicity, low cost, stability, reproducibility and sensitivity.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Effect of tert-alcohol functional imidazolium salts on oligomerization and fibrillization of amyloid beta (1-42) peptide - Said, Madhukar S.; Navale, Govinda R.; Yadav, Ashok; Khonde, Nilesh; Shinde, Sandip S.; Jha, Anjali (Biophysical Chemistry, 2020)
Imidazolium based IL's has gained vast interest in developing biological applications. Oligomerization and fibrillization of amyloid beta (1-42) peptide are mainly responsible for the extra-neuronal deposition of amyloid fibrils in neurodegenerative disorders like Alzheimer's disease (AD). Here, we report an effect of tert-BuOH-functional imidazolium ILs on oligomerization and fibrillization of amyloid beta (1-42) Peptide in vitro. In this study, a series of these [alkyl-(t)OHim][OMs] ILs with methyl sulphonate counter anion by varying alkyl chains were used. Among the seven protic ILs, four showed strong binding and inhibition activity for the formation of amyloid beta (1-42) aggregation by using Thioflavin T fluorescence binding assay. The secondary structural analysis of the peptide, pre-incubated with active ILs shows the loss of ordered beta-sheet amyloid structure. The longer alkyl chain ILs showed that an increased in amyloid binding and hence an inhibition effect on amyloid aggregation was enhanced. Thus, we propose that ILs could be presented as potential candidates for therapeutic intervention against Alzheimer's disease (AD).
Keywords: Aggregation; Amyloid beta (1-42) peptide; Biofilm inhibitor; Imidazolium ionic liquid

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology